2018
DOI: 10.1111/jfr3.12507
|View full text |Cite
|
Sign up to set email alerts
|

Trends in flood events and their relationship to extreme rainfall in an urban area of Sahelian West Africa: The case study of Ouagadougou, Burkina Faso

Abstract: Urban areas in Sahelian West Africa are highly vulnerable to extreme hydro‐meteorological events. In recent years, Burkina Faso has experienced several natural disasters with floods being the most frequent. This study investigates flood trends in Ouagadougou and their relationship to extreme rainfall events. Fourteen rainfall indices were analysed to characterise the frequency and intensity of extreme rainfall. A frequency analysis of annual maximum daily rainfall series was performed using three statistical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 34 publications
(43 reference statements)
3
42
0
Order By: Relevance
“…However, the nature of intraseasonal rainfall variability has changed over the Sahel during recent decades, with an observed increase in the frequency of very rainy MCSs separated by longer periods of little to no rainfall (Panthou et al 2014;Taylor et al 2017). More intense rain events carry increased risk of flooding, with observational studies suggesting that flood events over the Sahel have become more frequent over the past decades (Panthou et al 2014;Nka et al 2015;Panthou et al 2018;Tazan et al 2019;Wilcox et al 2018). Intense but temporarily sparse rain events can also deteriorate soil quality through nutrient runoff (Panagos et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, the nature of intraseasonal rainfall variability has changed over the Sahel during recent decades, with an observed increase in the frequency of very rainy MCSs separated by longer periods of little to no rainfall (Panthou et al 2014;Taylor et al 2017). More intense rain events carry increased risk of flooding, with observational studies suggesting that flood events over the Sahel have become more frequent over the past decades (Panthou et al 2014;Nka et al 2015;Panthou et al 2018;Tazan et al 2019;Wilcox et al 2018). Intense but temporarily sparse rain events can also deteriorate soil quality through nutrient runoff (Panagos et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The potential decrease in the number of rainy days and the consecutive wet days call for investment in water harvesting initiatives to ensure water availability for domestic and agricultural use during the dry periods. The potential for more heavy and intense precipitation events poses a risk to infrastructure over the study domain, which is vulnerable to floods [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand they bring the majority of rainfall required for agriculture (e.g., Laurent et al 1998;Laing et al 1999;Lafore et al 2011), but on the other hand, the most intense events can bring severe urban flooding (e.g., Engel et al 2017;Lafore et al 2017), damage to crops (e.g., Lobell and Gourdji 2012), and enhanced erosion (Panagos et al 2017). Panthou et al (2014) and Taylor et al (2017) have found a substantial recent increase in the frequency of these severe events, with other studies showing a corresponding increase in flood frequency (Nka et al 2015;Tazan et al 2019;Wilcox et al 2018). Globally, the frequency of intense rainfall events is expected to continue to increase as climate warms in response to rising anthropogenic carbon emissions (e.g., Kharin et al 2013;Kendon et al 2019), but at regional scales, the specific risks-measured for example by a ''defensible plausible range''-are largely unknown.…”
Section: Introductionmentioning
confidence: 99%